THE DYNAMICS OF BRYOPHYTES SPECIES DIVERSITY IN THE LOWLAND ECOSYSTEMS, CIBINONG SCIENCE CENTER-BOTANICAL GARDEN - Fandri Sofiana Fastanti; Tri Yuni Indah Wulansari (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Bryophytes are a group of plants generally with small sizes and spores as generative reproduction. There are three main groups of Bryophytes: liverworts or hepatics (Marchantiophyta), mosses (Bryophyta), and hornworts (Anthocerophyta). They are found in almost all ecosystems. Ecopark Cibinong Science Center-Botanical Garden (CSC-BG) is a lowland ecosystem protection area located in industrial cities. The bryophytes species that were carried out in 2009 and 2010 are inadequate. Re-exploration activity was carried out from June 2018 until January 2019 in all blocks of Ecopark. This study aims to report an update of bryophytes data in Ecopark. A total of 20 species of bryophytes were found in this research. Fissidens is the most common genus of bryophytes. There are 11 species of bryophytes and 9 species are new data records for Ecopark CSC-BG. This study updated bryophyte diversity data from Ecopark CSC-BG in 2009 and 2010, resulting in the discovery of 30 species (27 species mosses, 3 species liverworts), including 10 species not found in previous studies. There are no hornworts found in Ecopark CSC-BG.